2011
DOI: 10.1093/elt/ccr015
|View full text |Cite
|
Sign up to set email alerts
|

Weblogs: a tool for EFL interaction, expression, and self-evaluation

Abstract: The use of blogs in EFL learning and teaching has recently attracted a great deal of research attention. Previous research has demonstrated that blogs foster development of EFL skills. This study, which takes a sociocultural approach, focuses on EFL interaction. Specifically, the study aims to identify the interaction strategies that bloggers employ by exploring both teacher-initiated and studentinitiated interactions. An EFL undergraduate class at the University of Chile serves as the vantage point for discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 11 publications
3
21
0
2
Order By: Relevance
“…The visibility of his blog to his friends motivated Carl to closely monitor his accuracy [29]: I must proofread (the blog). When I fell asleep, suddenly I found that I had made a mistake, like, missing an 's' after plural nouns.…”
Section: Active Exploration Of More Learning Opportunitiesmentioning
confidence: 99%
“…The visibility of his blog to his friends motivated Carl to closely monitor his accuracy [29]: I must proofread (the blog). When I fell asleep, suddenly I found that I had made a mistake, like, missing an 's' after plural nouns.…”
Section: Active Exploration Of More Learning Opportunitiesmentioning
confidence: 99%
“…• motivating learners to study a foreign language and culture; • using a foreign language and the Internet to meet learners' cognitive interests; • sorting understanding, uncovering new ideas and drawing conclusions [3,10,11,12,13].…”
Section: Short Paper Blogs As a Means To Enhance Writing Skills In Efmentioning
confidence: 99%
“…In language learning and teaching, previous research demonstrated that blogging can promote interaction (Ducate & Lomicka, 2005;Miceli, Murray, & Kennedy, 2010;Trajtemberg & Yiakoumetti, 2011). Also, it can lend support to L2 learning in terms of enabling students to learn autonomously and collaboratively (Amir, Ismail, & Hussin, 2011;Baggetun and Wasson, 2006;Bhattacharya & Chauhan, 2010;Bakar, 2009;Godwin-Jones, 2003;Warlick, 2005), and to be motivated (Amir, et al, 2011;Bakar & Ismail, 2009), as well as to develop learner confidence (Bakar, 2009;Bakar, Latif, & Ya'acob, 2010).…”
Section: Introductionmentioning
confidence: 99%